Влияние нелинейностей на работоспособность систем скрытой передачи информации - Во Зуй Фук; Зиньковский, Ю. Ф.; Зинченко, М. В. (ХНУРЭ, 2016)
The perspectives and features of secure communication systems with chaotic signal as carrier waves usage are examined. It is shown that in the process of masking the data signal may have a preliminary non-linear transformation by tunnel diode, which is the part of the chaos generator. The levels of brought non-linear products and their ratio depend on the shape parameters of the diode characteristics, the operating point and the modulating signal amplitude. Normalized parameters that allow to develop efficient algorithms for minimizing unreliable modulation modes are introduced.
Keywords: системы скрытой передачи информации; генератор хаоса; нелинейность